Gestão de resíduos sólidos : um estudo nas empresas prestadoras de serviços de estética e beleza do bairro Rosa Elze em São Cristóvão (SE) - Santos, Jullyednna Menezes dos (2023)
This study has as its theme, the management of waste from beauty services in the search to aggregate conducts to users and the public involved and environmental sustainability. Given this, we have the following problem: What procedures occur in the management of solid waste in companies providing aesthetic and beauty services in the region of Rosa Elze in the municipality of São Cristóvão in Sergipe? The objective of this research is to identify the characteristics of companies and respondents; Verify the degree of knowledge of the interviewees about the impact of the waste generated on the environment; Identify the types of waste generated; Assess the conditions of collection, selection, packaging, storage, transportation, recycling and final destination of RS; and suggest solid and liquid waste management actions for the beauty salons analyzed in this research. There are many reports from owners of commercial establishments and residents of the region regarding the lack of selective collection of RS, and the non-preservation of environmental, social and possibly financial benefits. The research is documentary and field, descriptive and exploratory, with data collection through a semi-structured questionnaire, applied to professionals in the aesthetic area of the Rosa Elze neighborhood, in São Cristóvão/SE. With the research, it was evidenced that it is necessary to improve the management of waste and biosecurity so that the municipality should provide adequate selective garbage collection, so that professionals, owners and customers do not suffer damage to health due to environmental problems caused by the misuse of products and their services.